Spreading the Charm of 'Feelings of the Presidential Election' through TikTok Ahead of the Nahdlatul Ulama Congress - Rachmat Hidayat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The research was conducted by observing two candidates for general chairmanship of the Nahdlatul Ulama Executive Board (PBNU), each KH Said Aqil Siroj (Kiai Said) and Yahya Cholil Staquf or Gus Yahya in implementing political marketing strategies through TikTok social media. All observation data were collected from the beginning of the month, until December 20, 2021, ahead of the 34th Congress in Lampung Province. Observations were made using netnographic techniques, analyzed by qualitative research methods. The TikTok social media channel is part of changing people's behavior in the current digitalization era. This was also done to Kiai Said and Gus Yahya, two candidates for the general chairmanship of PBNU in democracy in the digital space. Spreading mutual charm, similar to the battle for the Presidential Election (Pilpres) in conveying messages to the public or netizens, including nahdliyin residents.